Niat Berpindah Nasabah yang Termigrasi Paksa ke Bank Syariah Indonesia - Berliana Fajar Nur Endah Sari; Hendy Mustiko Aji (Jurnal Manajerial, 2023)
Background – The merger that was done by BUMN Islamic Banks in Indonesia to form Bank Syariah Indonesia (BSI) has forced the customers to switch to the new system. This switch may create resistance. As this phenomenon is still new, therefore, there are still very limited studies that investigate it. Aim – This study is aimed to investigate factors that influence customer switching intention to Bank Syariah Indonesia (BSI). Design / Methodology / Approach – This study collected 106 respondents and the data is analyzed using PLS-SEM. The purposive sampling technique is chosen by creating criteria for the sample, such as ex-Bank Syariah Mandiri, BRI Syariah, and BNI Syariah customers who are forcedly switched to Bank Syariah Indonesia (BSI). Findings – This study shows that trust has a significant effect on satisfaction, but it does not influence switching intention. Satisfaction is significantly influenced by service quality, but it has a negative effect on switching intention. Interestingly, service quality also does not influence switching intention. Conclusion - This study concludes that customer switching intentions are significantly influenced by customer satisfaction, but not by trust and service quality. Research Implication – The findings of this study are expected to be used by Bank Syariah Indonesia (BSI) managers in designing a customer loyalty program. So that, the customers who are forcedly switched can stay. Limitations – Most of the respondents in this study are from Java Island. This unbalanced proportion might affect the validity of the findings.